Immediate Unprotected Weightbearing After Open Reduction Internal Fixation of Ankle Fractures: A Prospective Trial - Vu (Brian) Le MD, FRCSC; Darius Viskontas MD FRCSC; Ryan Lohre MD; James R. Yan MD, FRCSC; Trevor Stone MD, FRCSC; Bertrand Perey FRCS; Farhad O. Moola MD, FRCSC; Dory Boyer BSc MD FRCSC; Mike M. Lemke MD; Kelly L. Apostle MD FRCSC (Foot & Ankle Orthopaedics, 2023)
Category: Trauma; Ankle Introduction/Purpose: Ankle fractures are among the most common orthopaedic injuries treated surgically, with indications well- established. However, post-operative care protocols remain controversial and vary widely between surgeons. This prospective controlled trial compared functional outcomes of the local institutional standard (control group) of nonweightbearing (NWB) for two weeks in a short leg splint followed by weightbearing as-tolerated (WBAT) in a boot with range of motion (ROM), versus immediate unprotected weightbearing (IMWB). Methods: 40 consecutive patients undergoing ankle fracture open reduction internal fixation (ORIF) at a single level-1 trauma center meeting inclusion and exclusion criteria were enrolled into the control group, and the next 40 consecutive patients were enrolled in the IMWB group. The study sample size was powered to detect a statistically significant difference in the Olerud- Molander score (OMAS), the primary study outcome. Secondary outcome measures included the Euroquol-5D (EQ5D) self reported patient score and Work Productivity and Activity Impairment: Specific Health Problem (WPAI:SHP) scores, ankle ROM, wound complications, time to return to work, radiograph measurements and loss of fracture reduction. Patients underwent ankle ORIF with surgical technique and implant choice left to the surgeon’s discretion. Postoperative follow-ups were done at 2, 6, and 12 weeks. Results: Demographics of the two groups were similar except for the control group having 4 patients with type II diabetes and the IMWB group having none. There was no statistically significant difference in OMAS at any time point. There were also no statistically significant differences in the EQ5D or WPAI:SHP scores, ROM, time to return to work, or radiographic measurements at any time point. The IMWB group had 5 superficial wound complications versus 1 in the control group. There were 2 cases of loss of reduction in the IMWB group versus none in the control group. Both loss of reductions were determined to not be related to the post operative protocol. Conclusion: Immediate unprotected weightbearing after ORIF of ankle fractures results in equivocal functional outcomes compared with 2 weeks of NWB followed by protected weightbearing and ROM over the first 3 postoperative months. An increased number of wound healing complications was seen in the IMWB group which requires further investigation.